Agent-based modelling to simulate the socio-economic effects of implementing time-of-use tariffs for domestic water. (November 2022) - Vidal Lamolla, Pol; Popartan, Alexandra; Perello-Moragues, Toni; Noriega, Pablo; Saurí, David; Poch, Manel; Molinos-Senante, Maria
Highlights: A time-of-use tariff was modelled using agent-based approach. Different socio-cognitive profiles and types of households were modelled. Annual domestic water use would be reduced by 17.2%. Abstract: Designing and implementing innovative and effective policies to reduce domestic water demand is vital to enhance sustainability of cities. Past research has shown that Time-of-Use Tariffs (TOUT) is a powerful tool to reduce water consumption in urban settings. Nevertheless, the effectiveness of this dynamic water pricing approach might be influenced by the socioeconomic conditions and preferences of households. To shed light on this issue, this paper employed an agent-based modelling method to simulate the possible socioeconomic effects of implementing TOUT in a Spanish municipality. The types of households were characterized according to size, number of inhabitants, income and to socio-cognitive profiles (clients, techno-solutionist, committed and environmentalist). Results from the modelling indicate that the implementation of a TOUT system would reduce domestic water use by 17.2%. However, this reduction was not homogenous for the socioeconomic groups of households defined. Low-income households are those who most reduced their water consumption (25.0%) but had the lowest water bill savings (9.3%). By contrast, high-income households present the largest water bill savings (11.9%) but the lowest reduction in water use (10.4%). The findings of this study evidence the importance of considering the socioeconomic and socio-cognitive differences among water users to evaluate the effectiveness of TOUTs.